A systematic review exploring the patient decision‐making factors and attitudes towards pre‐implantation genetic testing for aneuploidy and gender selection. (30th August 2020) - Bracewell‐Milnes, Timothy; Saso, Srdjan; Jones, Benjamin; Cato, Sarah; Parikh, Riya; Thum, Meen‐Yau; Johnson, Mark; Almeida, Paula; Norman‐Taylor, Julian; Nikolaou, Dimitrios
Abstract: Introduction: Pre‐implantation genetic testing for aneuploidy (PGT‐A) is in high demand worldwide, with ongoing debate among medical societies as to which patient groups it should be offered. The psychological aspects for patients regarding its use, lag behind the genomic technological advances, leaving couples with limited decision‐making support. The development of this technology also leads to the possibility for its utilization in gender selection. Despite the controversy surrounding these issues, very few studies have investigated the psychological aspects of patients using PGT‐A. Material and methods: This systematic review provides an up‐to‐date analysis of the psychosocial aspects surrounding PGT for aneuploidy and sex selection, as well as decision‐making factors. A systematic search of English peer‐reviewed journals of three computerized databases were undertaken following PRISMA guidelines. The qualitative data were extracted using thematic analysis. PROSPERO Registration number: CRD42019126439. Results: The main outcome measures were patients' motivations, decision‐making factors, attitudes and experiences surrounding the use of PGT for aneuploidy and sex selection. Ten studies were included, four for PGT‐A and six for sex selection. Attitudes towards PGT‐A were positive, with the main motivating factors being decreasing miscarriage rate, reducing the risk of termination of pregnancy and reducing the time to pregnancy. Consistently raised concerns regarding PGT‐A were the financial burden and moral beliefs. The vast majority of patients felt sufficiently knowledgeable to make the decision; however, studies did reveal that a minority mis‐interpreted certain potential benefits of PGT‐A. Studies investigating PGT for sex selection predominantly reported the main motivation was to achieve gender balance within the family dynamic, with most studies finding no difference between couples using PGT for gender selection to have male or female offspring. Conclusions: Although this systematic review was limited by the small number of studies investigating this topic, a significant minority of patients appeared to misunderstand certain benefits and limitations of PGT‐A. Fertility clinics must ensure they provide adequate counseling to all patients using PGT‐A. With the use of PGT‐A on the rise globally, there is a need to develop decision support tools for couples who have an increasing number of genetic testing options becoming available to them.